2006
DOI: 10.1177/0363546505282616
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-six-Year Results after Broström Procedure for Chronic Lateral Ankle Instability

Abstract: Background The procedure described by Broström has been used to address chronic lateral ankle instability; the long-term results of this procedure have not been reported. Hypothesis The Broström procedure provides good results over the long term for active patients with chronic lateral ankle instability. Study Design Case series; Level of evidence, 4. Methods Thirty-one male patients (32 ankles) who underwent the Broström procedure for chronic lateral ankle instability while enrolled as students at the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(151 citation statements)
references
References 21 publications
3
133
1
5
Order By: Relevance
“…Multiple studies demonstrated satisfaction rate of over 90% after modified Broström procedure [66,68,93]. Although the Broström procedure is generally considered a highly successful operation, the recovery typically involves a prolonged period of immobilization and rehabilitation.…”
Section: Anatomic Ligament Repairmentioning
confidence: 99%
“…Multiple studies demonstrated satisfaction rate of over 90% after modified Broström procedure [66,68,93]. Although the Broström procedure is generally considered a highly successful operation, the recovery typically involves a prolonged period of immobilization and rehabilitation.…”
Section: Anatomic Ligament Repairmentioning
confidence: 99%
“…Anatomic repair of the ATFL using the Bröstrom-Gould modifi ed technique in the presence of CFL insuffi ciency has been shown to be highly successful with reports of 93 % excellent results at an average of 64 months follow-up [ 102 ], 80 % excellent or good results at 6 years follow-up [ 103 ], and 91 % good-to-excellent results at 26 years follow-up [ 104 ]. Major advantages of this method are its simplicity and small incision size [ 105 ].…”
Section: Lateral Ligament Instabilitymentioning
confidence: 99%
“…The use of a periosteal flap from the fibula, as well as autologous free tendon graft and allograft augments, has also been well described with favorable results [75,76,78] . Furthermore, sustained excellent patient outcomes have been reported by Bell et al [95] at greater than 20-year follow-up, and this procedure has demonstrable success in high-demand athletes [96] . Anatomic tenodesis procedures have recently been the subject of multiple investigations and have demonstrated promising results [54,74,87,88,97] .…”
Section: Chronic Ankle Instability Treatmentmentioning
confidence: 65%